Linkage between university and community in the training process of dental students from the teachers' perspective - Silvia Marisol Gavilánez Villamarín; Jaime Fernando Armijos Moreta; Mery Alexandra Mendoza Castillo; Amalia Fernanda Vera Veloz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Foundation: the connection projects with society carried out by Ecuadorian universities are an opportunity for service and an alternative to bring their students closer to the community. Objective: to describe the grant value by teachers on the link between university and community in the dental students training process. Methods: observational, descriptive and cross-sectional study of dentistry teachers at the Los Andes Regional Autonomous University from January to June 2022. The population of 15 teachers at the Santo Domingo campus. Results: 100% of the teachers considered that the university-community connection allows the application of the acquired knowledge. The short duration of the periods (100%) and the lack of empowerment of teachers (100%) were indicated as weaknesses; and as positive elements the promotion of microenterprises among students (100%) and comprehensive development in the professional future (100%). Feedback between the university and the community (100%) and changes in training paradigms (100%) were identified as needs. Conclusions: teachers identify the university-community link as an opportunity of great value in the dental students training, preparing them based on the social problems solution typical of professional practice. The lack of empowerment and the conception of short-term projects are recognized as weaknesses, which demands transformations in current teaching dynamics, based on feedback between academia and society.